Abu Ali Muhammad bin Hafs bin Numair bin Abdul Aziz Al-Ruhmi Al-Amiri Al-Hanafi Al-Yamani (280 AH), the writer, novelist, and the remaining of his poetry - Kamel, Prof Dr. Qasim Mohammed (Thi Qar Arts Journal, 2023)
For every language, there are scholars who have exerted great or small efforts in preserving and revitalizing it. Arabic is not an exception among languages, and its scholars did not downplay its importance compared to others, especially if they were among the pioneers in this endeavor. Most of these scholars have gained their share of fame, widespread recognition, and the dissemination of their works. However, not many of them were fortunate in this regard, especially those who lived in the early centuries. Among these scholars is Abu Ali Al-Yamami, the subject of this research. Despite the breadth of his expertise, encompassing language narration and eloquence, as well as his involvement in literature and poetry, along with a long lifespan that spanned nearly a century, from the late second century to the end of the third century of the Islamic calendar, we can still observe that we do not find much about him in literary and linguistic texts. Instead, what we find are scattered fragments of narratives, news, and poems, representing only a small part of his contributions to language and literature. Nevertheless, these fragments offer us a clear picture of a world populated by Arabic scholars who actively engaged in poetry and storytelling during their era. Their influence extended widely, and we can see scholars referencing their work in their linguistic publications throughout the ages. Therefore, we decided to collect these scattered pieces to introduce this narrative poet and to shed light on his life and the narratives that have reached us.